The untold story of Washington's surprise attack the daring crossing of the Delaware River - Kravitz, Danny (North Mankato, MN Compass Point Books, 2015)
Presents the story of General George Washington's crossing of the Delaware River, and how this daring act boosted sagging morale, shocked the British, and convinced potential allies such as France that the Americans meant business
A gift from book Africa
Famous People
1 2 13
NEW_ZTN_GN
Keywords: Washington, George -- 1732-1799; Washington, George -- 1732-1799 -- Military leadership; Washington, George -- 1732-1799 -- Military leadership -- Juvenile literature